The Influence of the Use of Village Funds on Village Development and Empowerment of the Kedonganan Traditional Village Community - Windusara, Putu Ratna (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This thesis is entitled "The Influence of the Use of Village Funds on Village Development and Empowerment of the Kedonganan Traditional Village Community". This research discusses the influence of village fund allocation on the level of Village Development and Empowerment of the Kedonganan Traditional Village Community. This research used qualitative research methods as well as book references that were relevant to the problem. The data collected is qualitative data, so it is processed into quantitative descriptive data. Determining the sample in this study used the Slovin technique, because the population was too large and difficult to reach one by one, the number of samples taken in this study was 98 respondents. The data collection techniques used were observation and questionnaires. Technical data analysis uses regression analysis. The validity of the data is obtained through validity tests and reliability tests. Based on the results of the research carried out, it was concluded that the hypothesis which states "The use of village funds is positive and significant on the level of Village Development and Empowerment of the Kedonganan Traditional Village Community", has been proven empirically and is acceptable. This is proven by the results of SPSS data processing which shows a calculated t value of 2.869 with Sig 0.005, for the Village Development variable and 3.492 with Sig 0.001, for the Community Empowerment variable. Which means that the calculated t value is greater than the t table (1.984) so that the influence of the Village Fund variable on the level of Village Development and Community Empowerment is significant.